Sigmoid volvulus; a rare complicated presentation of Hirschsprung's disease: A case report. (December 2021) - Zain, Mostafa; Abouheba, Mohamed
Abstract: Introduction: Sigmoid volvulus (SV) is a rare complication of Hirschsprung's disease (HD) with only 31 cases have been reported in the English literature. Although its diagnosis is challenging, unrecognized SV is a life-threatening condition requiring early recognition to decrease morbidity and mortality. Presentation of case: A 14-year-old male presented to our emergency department with massive abdominal distention. Plain erect abdominal X-ray showed massive colonic distention with multiple fluid levels. Colonoscopy failed to pass beyond 15 cm after entering dilated sigmoid loop. Open surgical exploration was done through a lower midline incision and revealed SV with massive distention of the entire colon. After detorsion, we found a markedly dilated sigmoid colon with an evident discrepancy at the lower sigmoid. Due to massive colonic dilatation, the decision was made for terminal ileostomy. Histopathological examination of biopsy from the narrow segment demonstrated aganglionosis and hypertrophic submucosal neural fibers confirming the diagnosis of HD. Discussion: SV is a rare serious complication of HD. Unrecognized SV is a serious life-threatening condition, so it should be considered in children with acute or recurrent abdominal pain, distension, constipation and vomiting as early recognition and management of volvulus is essential to decrease morbidity. Conclusion: The presented case highlights the possibility of SV as a rare complication of HD should be considered especially in children with a history of chronic constipation and abdominal distension who present with acute colonic distension and failure to decompress despite rectal washes. Highlights: Sigmoid volvulus is a rare complication of Hirschsprung's disease with a reported prevalence of 0.66%. Prompt diagnosis of the acute of volvulus decreases morbidity and increases survival. Sigmoid volvulus should be considered in children presenting with acute intestinal obstruction. In children with sigmoid volvulus, Hirschsprung's disease should be suspected, and proper evaluation is required.